2021
DOI: 10.3389/fonc.2021.651119
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Adverse Pathologic Features and Clinical Outcomes of Resectable Pancreas Cancer With Preoperative CA 19-9

Abstract: BackgroundWe evaluated preoperative CA 19-9 levels in patients with resected pancreatic cancer to analyze whether they were predictive of clinical outcomes and could help select patients for additional therapy. We hypothesized that elevated CA 19-9 would be associated with worse pathologic findings and oncologic outcomes.MethodsThis study assessed 509 patients with non-metastatic pancreatic adenocarcinoma who underwent resection at our institution from 1995-2011 and had preoperative CA 19-9 recorded. No patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 47 publications
0
11
0
1
Order By: Relevance
“…Using CA 19.9 levels at the cut-off value of 55 U/mL, they found a significant association between this marker and the pT stage. More specifically, CA 19.9 levels higher than the cut-off resulted associated with pT stage ≥ 3 ( p = 0.0005) [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Using CA 19.9 levels at the cut-off value of 55 U/mL, they found a significant association between this marker and the pT stage. More specifically, CA 19.9 levels higher than the cut-off resulted associated with pT stage ≥ 3 ( p = 0.0005) [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The advancing literature has established the prognostic value of CA 19-9 in LAPAC patients managed with chemotherapy or C-CRT plus/minus surgery. [16][17][18][19][20][21][22][23] Although different CA 19-9 cutoffs were utilized, results of past investigations confirmed the significant association between higher CA 19-9 levels and reduced survival results in PAC patients. [19][20][21][22][23] Like our study, the researchers of the aforementioned landmark Charité Onkologie 001 (CONKO-001) and RTOG 97-04 randomized trials chose the CA 19-9 ≤ 90 U/mL as the cutoff level for prognostic stratification of such patients.…”
mentioning
confidence: 92%
“…[16][17][18][19][20][21][22][23] Although different CA 19-9 cutoffs were utilized, results of past investigations confirmed the significant association between higher CA 19-9 levels and reduced survival results in PAC patients. [19][20][21][22][23] Like our study, the researchers of the aforementioned landmark Charité Onkologie 001 (CONKO-001) and RTOG 97-04 randomized trials chose the CA 19-9 ≤ 90 U/mL as the cutoff level for prognostic stratification of such patients. 16,17 Authenticating the CA 19-9 as a prognostic factor, Choi et al reported that the pretreatment higher CA 19-9 levels were associated with significantly reduced survival outcomes in their three-tiered nomogram consolidating the SUVmax, radiotherapy dose, and CA 19-9 in a gathering of 426 LAPAC patients undergoing C-CRT.…”
mentioning
confidence: 92%
See 2 more Smart Citations